Factors affecting utilization of dental care among 6-12-year-old school children in Bangarpet taluk, Karnataka - C Priyadarshini; Manjunath P Puranik; S R Uma (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral diseases qualify as major public health problems owing to their high prevalence and incidence worldwide. Access to oral healthcare refers to patient's ability to obtain or utilize oral healthcare. Aim: To assess the dentition status and treatment needs among 6-12-year-old school children and to assess the factors affecting utilization of dental care among parents. Materials and Methods: A cross-sectional survey was conducted among 420 school children (6-12 years) in Bangarpet taluk. Factors affecting utilization of dental care were assessed using a validated questionnaire and dentition status and treatment needs was recorded according to WHO 1997 proforma. Descriptive and inferential statistics were used. Results: The proportion of children with dmft was 62 (30%) and 54 (26%) in urban and rural children, respectively whereas the proportion of children with DMFT was 48 (23%) and 79 (38%) in urban and rural children, respectively. Among urban children 99 (47%) did not need any treatment when compared to 87 (41%) rural children. Around 32 (15.2%) needed one surface filling in urban children and 20 (9.52%) in rural children. About 30 (14.28%) urban and 40 (19.04) in rural children needed preventive care, respectively. Most of the parents were not aware of fluoride content in the toothpaste. Parents agreed that maintenance of oral health is their duty. There was a significant difference between urban and rural parents for the barriers "no time to visit" (P = 0.0002), "affects my work" (P = 0.048) and "scared of injection" (P = 0.0033). Dental visits were found to be low in both urban 37 (18%) and rural 56 (27%) children. Conclusion: The caries experience was similar among urban and rural children. Most of the children required restorative and preventive care. Fear of injection and lack of time to visit dentist were the major barriers to parents for utilization of dental care. Hence, integrated approach is suggested to strengthen preventive and early intervention of oral disease.